Changing Gender Attitudes: The Long-Run Effects of Early Exposure to Female Classmates - Javier Garcia-Brazales (ZBW – Leibniz Information Centre for Economics, 2021)
Identity norms are an important cause of inequalities and talent misallocation. I lever- age a unique opportunity to observe students exogenously allocated to classes across a close-to-nationally-representative set of Vietnamese schools to show that more exposure to female peers during childhood causally decreases the extent of agreement with tradi- tional gender roles in the long-run. This shift in attitudes is accompanied by changes in actual behavior: employing friendship nominations I find that male children have more female friends and spend more time with them outside school. Moreover, both their intensive and extensive margin contributions to home production increase in the short- and the long-run. These results are novel in the attitudes formation and in the long- term effects of peers literature and are important in informing optimal class allocation. Academic spillovers from female classmates are much weaker.
More recent version: http://hdl.handle.net/10419/266544
Keywords: I24; I25; J16; 330; Long-term Peer Effects; Gender Roles; Attitudes Formation